2016
DOI: 10.1109/led.2016.2619738
|View full text |Cite
|
Sign up to set email alerts
|

Flexible In–Ga–Zn–O-Based Circuits With Two and Three Metal Layers: Simulation and Fabrication Study

Abstract: Abstract-The quest for high-performance flexible circuits call for scaling of the minimum feature size in Thin-Film Transistors (TFTs). Although reduced channel lengths can guarantee an improvement in the electrical properties of the devices, proper design rules also play a crucial role to minimize parasitics when designing fast circuits. In this letter, systematic Computer-Aided Design (CAD) simulations have guided the fabrication of highperformance flexible operational amplifiers (opamps) and logic circuits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…To test this, the op-amp connected as a unit gain buffer. [12], [15] and higher than [10], [11] these. Even though having SG structured TFT, in [12], and [15] still shows better yield than this current report.…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…To test this, the op-amp connected as a unit gain buffer. [12], [15] and higher than [10], [11] these. Even though having SG structured TFT, in [12], and [15] still shows better yield than this current report.…”
Section: Resultsmentioning
confidence: 82%
“…Zysset et al [10] reported a 16-TFT op-amp in the flexible substrate with the A v of 18.7 dB and f c of 108 kHz. Cantarella et al [11] reported another 13-TFT op-amp in the flexible substrate with the A v of 19.4 dB and f c of 6.9 kHz. Recently, Kim et al [12] demonstrated a solution processed op-amp on the glass substrate with 19-TFTs and using direct light pattering (DLP) method with the A v of 24.6 dB and f c of 0.47 kHz.…”
Section: Introductionmentioning
confidence: 99%
“…The TFTs and inverters (NOT gates) are based on bottom‐gate inverted staggered configuration (see Figure a and Device Fabrication section). IGZO is chosen as semiconductor for its high electrical performance, low deposition temperature, and large area capability, representing a good candidate as semiconductive material on flexible substrates . The transfer and output characteristics of an IGZO‐based TFT directly fabricated on a mesa‐shaped PDMS membrane are shown in Figure b,c.…”
mentioning
confidence: 99%
“…Flexible thin-film transistors (TFTs) hold great potential for numerous emerging applications, including flexible and paper-like displays, 1 wearable and textile integrated systems, 2,3 smart labels and intelligent packaging, 2,4 epidermal devices, 5 electronic skins, 6 as well as imperceptible, biomimetic, and transient implants. [7][8][9] In recent years tremendous advances have been achieved through the use of metal oxide semiconductors as the channel materials 10 as they combine processing versatility 11 and high electron carrier mobility 12 leading to realization of numerous functional systems including large-area digital [13][14][15] and analog [15][16][17] circuits composed of hundreds of TFTs. 13 Despite the impressive progress, however, further developments are hampered by the lack of p-type semiconductors with performance and stability comparable to those found in their n-type counterparts.…”
mentioning
confidence: 99%